Explaining the variety of social policy responses to economic crisis: How parties and welfare state structures interact - Peter Starke; Alexandra Kaasch; Franca van Hooren (Universität Bremen, Collaborative Research Center 597 - Transformations of the State, 2011)
This paper maps and explains the reactions of four welfare states - Australia, Belgium, the Netherlands and Sweden - to three global crisis situations - the oil shocks of the 1970s, the worldwide recession of the early 1990s, and the financial crisis from 2008 onwards. Two main conclusions follow from the analysis: First, using a comprehensive typology of social policy reactions to crises, we show that crisis reactions were surprisingly diverse. There is no uniform policy response, as policies range from retrenchment through non-response to welfare state expansion. Second, explaining the variation regarding expansion vs. retrenchment we focus on the partisan composition of government, and the size of the existing welfare state, which may operate as an important automatic stabilizer during recessions. While none of these factors alone is sufficient, their interaction is able to explain most of the specific social policy responses adopted in the four countries studied. – – Das Arbeitspapier beschreibt und erklärt die Reaktionen von vier Wohlfahrtsstaaten - Australien, Belgien, die Niederlande und Schweden - auf drei globale Krisensituationen - die Ölpreisschocks der 1970er Jahre, die weltweite Rezession in den frühen 1990ern und die Finanzkrise nach 2008. Zwei Schlussfolgerungen können gezogen werden: Erstens zeigen wir, basierend auf einer umfassenden Typologie sozialpolitischer Krisenreaktionen, dass Krisenreaktionen überraschend unterschiedlich ausfielen. Es gibt keine einheitliche Krisenantwort, Reaktionen reichen vielmehr von Kürzungen, über bewusste Nicht-Reaktion, bis hin zu sozialpolitischem Ausbau. Zweitens konzentrieren wir uns zur Erklärung der Variation im Hinblick auf Rückbau und Ausbau einerseits auf die parteipolitische Zusammensetzung der Regierung und andererseits auf die Größe des existierenden Wohlfahrtsstaats, der in Zeiten wirtschaftlicher Rezession als wichtiger automatischer Stabilisator wirken kann. Obgleich keiner dieser Faktoren allein ausreicht, ist ihre Interaktion in der Lage, die meisten spezifischen sozialpolitischen Reaktionen der vier Länder zu erklären.
Keywords: 300